2021
DOI: 10.1177/00302228211048667
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Experiences Towards Death of Healthcare Professionals Working in Neonatal Intensive Care Units

Abstract: Background Death is an integral part of neonatal intensive care units’ (NICUs) environment and little it is known about NICU’s staff death concepts. Aim To investigate attitudes and experiences towards death of healthcare professionals (HPs) working in NICUs Design Totally 131 participants from six hospitals were included in the study. Research instruments were a questionnaire designed by the authors and the scale Death Attitude Profile-Revised. Results Gender, marital and educational status, frequent contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, accepting mortality and viewing death as an inevitable part of the human experience rather than something to be feared or avoided excessively can be emotionally difficult, especially for midwives who work in settings where maternal, perinatal, and neonatal deaths occur, resulting even in occupational trauma [53]. In a previous Greek study as well, conducted among healthcare professionals working in neonatal intensive care units [27], including midwives in the highest percentage, it was found that greater 'frequency of care related to end of life neonates' was significantly associated with greater fear of death, while neutral acceptance was not associated significantly with any of the studied characteristics and experiences. Finally, higher GSES scores were significantly associated with higher scores on the CD-RISC, indicating that midwives with higher self-efficacy also tend to exhibit greater resilience in coping with the demanding and stressful nature of their profession.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, accepting mortality and viewing death as an inevitable part of the human experience rather than something to be feared or avoided excessively can be emotionally difficult, especially for midwives who work in settings where maternal, perinatal, and neonatal deaths occur, resulting even in occupational trauma [53]. In a previous Greek study as well, conducted among healthcare professionals working in neonatal intensive care units [27], including midwives in the highest percentage, it was found that greater 'frequency of care related to end of life neonates' was significantly associated with greater fear of death, while neutral acceptance was not associated significantly with any of the studied characteristics and experiences. Finally, higher GSES scores were significantly associated with higher scores on the CD-RISC, indicating that midwives with higher self-efficacy also tend to exhibit greater resilience in coping with the demanding and stressful nature of their profession.…”
Section: Discussionmentioning
confidence: 99%
“…However, a limited body of evidence exists concerning midwives and the aforementioned psychometric tools, especially in our country. To the best of our knowledge, only a single Greek study [ 27 ] has incorporated midwives along with other healthcare professionals, all staff members of Neonatal Intensive Care Units, and examined them in relation to attitudes towards death. Regrettably, the limited number of participants (N = 131) made it impossible to conduct subgroup analysis across specialties, thus preventing the drawing of specific conclusions for midwives alone.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating neonatal palliative care in healthcare systems requires advanced training and education for healthcare professionals. Physicians, midwives, nurses, psychologists, and other professionals often complete continuing education and professional development programs that promote patient- and family-centered services [ 2 , 5 , 15 ]. Although relevant training programs differ from one European country to another, there are fundamental principles that should underpin all training programs in palliative care.…”
Section: Editorialmentioning
confidence: 99%
“…An exception is an interdisciplinary postgraduate program [ 5 ]. Healthcare professionals need advanced and evidence-based training to become an integrated part of their undergraduate, postgraduate, and continuing education programs because education equips healthcare professionals with the skills and knowledge they need to provide compassionate and effective care to neonates and their families [ 1 , 15 ].…”
Section: Editorialmentioning
confidence: 99%
“…In reviewing the existing literature, we found several studies that examined HPs' attitudes toward death [3,[29][30][31][32][33][34][35][36]. However, to the best of our knowledge, only one Greek study [37] has included midwives, among other HPs, working in Neonatal Intensive Care Units. Therefore, it is observed that Greek midwives remain an underexplored territory.…”
Section: Introductionmentioning
confidence: 99%